Type speaks - Heller, Steven 1950-; Anderson, Gail 1962- (Abrams, 2021)
An essential resource to using contemporary typefaces for effective communication0Type is the handwriting of the 21st century, lending its expressive voice to the language of all written communication. Type Speaks is the first book to explore type as a medium that conveys emotions, concepts, and ideas, filled with hundreds of new fonts available through digital foundries. Some exude joy, radiate serenity, or jangle the nerves; some sell or persuade or command or seduce. More than ever before, a great range of type choices, both conventional and unconventional, is available to graphic design professionals and nonprofessionals alike. In this new world, Type Speaks will be an essential reference for anyone crafting messages in words
Keywords: Font; Typografie; Letter; Typography; Graphic design; Communication studies; Type and type-founding; LANGUAGE ARTS & DISCIPLINES / Communication; Enzyklopädie; Bildband